2022
DOI: 10.3390/ani12050629
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Puppies: Demographic Characteristics, Health and Early Life Experiences of Puppies Acquired during the 2020 Phase of the COVID-19 Pandemic in the UK

Abstract: The UK recorded sharp rises in puppy purchasing during the 2020 phase of the COVID-19 pandemic, with many first-time dog owners purchasing puppies to improve their mental health during this challenging period. Government restrictions on movement and social interaction during the pandemic led to animal welfare concerns over puppies’ reduced time-sensitive exposures to key environmental and social stimuli during their critical developmental period. This study aimed to compare demographics, health and early-life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 50 publications
4
35
0
Order By: Relevance
“…Results from this study may also be applied to owners that have experienced a period out of work with altered routines, as separation-related effects would be similar in these cases. Brand et al [3] similarly found that there were negative implications of separation shown; however, with this research focusing on adult dogs, it was positive implications were also identified, with some dogs able to cope better when left alone after lockdown. This study may also be comparable when owners move property, whether this is from a quiet to a busier area or vice versa.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Results from this study may also be applied to owners that have experienced a period out of work with altered routines, as separation-related effects would be similar in these cases. Brand et al [3] similarly found that there were negative implications of separation shown; however, with this research focusing on adult dogs, it was positive implications were also identified, with some dogs able to cope better when left alone after lockdown. This study may also be comparable when owners move property, whether this is from a quiet to a busier area or vice versa.…”
Section: Discussionmentioning
confidence: 64%
“…Due to lockdown restrictions, they were able to spend more quality time with their dog and, as a whole, participants enjoyed the additional time spent with their companion. However, these interactions may have negative long-term effects as increased dog-owner interactions could result in increased separation issues, as seen in "pandemic puppies" [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has also been reported to reduce levels of puppy socialisation. For example, Brand et al (2022) [ 41 ] found that “Pandemic Puppies” were less likely to have attended puppy training classes or received exposure to people from outside the home before 16 weeks of age. This raises concerns for the future welfare of these puppies and highlights the need for more research into socialisation programs [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In January 2021, the provision of essential veterinary care in England was no longer considered as a criterion for the crucial worker status (9), further disrupting the provision of veterinary care. Many dog owners acquired dogs during the pandemic, therefore further disruptions occurred at a time when the UK's dog population, and plausibly the demand for veterinary care, also increased (10,11).…”
Section: Introductionmentioning
confidence: 99%